Biotechnologies for plant mutation breeding : protocols - Jankowicz-Cieslak, Joanna; Tai, Thomas H.; Kumlehn, Jochen; Till, Bradley J. (Springer, 2017)
This book is open access under a CC BY-NC 2.5 license. This book offers 19 detailed protocols on the use of induced mutations in crop breeding and functional genomics studies, which cover topics including chemical and physical mutagenesis, phenotypic screening methods, traditional TILLING and TILLING by sequencing, doubled haploidy, targeted genome editing, and low-cost methods for the molecular characterization of mutant plants that are suitable for laboratories in developing countries. The collection of protocols equips users with the techniques they need in order to start a program on mutation breeding or functional genomics using both forward and reverse-genetic approaches. Methods are provided for seed and vegetatively propagated crops (e.g. banana, barley, cassava, jatropha, rice) and can be adapted for use in other species.- Resumé vydavatel
Keywords: rostlinná biotechnologie; šlechtění rostlin; geneticky modifikované rostliny; plant biotechnology; plant breeding; genetically modified plants; elektronické knihy; sborníky; electronic books; papers of several authors